2015
DOI: 10.2500/ajra.2015.29.4111
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Steroids and the Myth of Mucosal Atrophy: A Systematic Review of Original Histological Assessments

Abstract: The concept of nasal mucosal atrophy is poorly defined and there is no histological evidence for deleterious effects from INCS use on human nasal mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 75 publications
0
12
0
2
Order By: Relevance
“…This review demonstrated that from 34 studies that assessed the nasal mucosa via biopsy, including 11 randomized controlled trials, 5 cohorts, and 20 case series (with a duration of treatment ranging from 5 days to 5.5 years), no atrophic changes were observed. There were 2 studies that demonstrated the protective effects of INCS against remodeling changes such as squamous metaplasia 1584 . This protection against mucosal remodeling 1584 is relevant as such changes have been implicated in poorer clinical outcomes 1585 …”
Section: Chronic Rhinosinusitis With Nasal Polyps (Crswnp)mentioning
confidence: 99%
See 1 more Smart Citation
“…This review demonstrated that from 34 studies that assessed the nasal mucosa via biopsy, including 11 randomized controlled trials, 5 cohorts, and 20 case series (with a duration of treatment ranging from 5 days to 5.5 years), no atrophic changes were observed. There were 2 studies that demonstrated the protective effects of INCS against remodeling changes such as squamous metaplasia 1584 . This protection against mucosal remodeling 1584 is relevant as such changes have been implicated in poorer clinical outcomes 1585 …”
Section: Chronic Rhinosinusitis With Nasal Polyps (Crswnp)mentioning
confidence: 99%
“…There were 2 studies that demonstrated the protective effects of INCS against remodeling changes such as squamous metaplasia 1584 . This protection against mucosal remodeling 1584 is relevant as such changes have been implicated in poorer clinical outcomes 1585 …”
Section: Chronic Rhinosinusitis With Nasal Polyps (Crswnp)mentioning
confidence: 99%
“…A review of histological assessments of nasal mucosa after intranasal steroids reported that there was no evidence for mucosal atrophy, while increased glandular hyperplasia and squamous metaplasia may represent a reversal of the remodeling, rather than atrophy, of the nasal airway. 28,29 Steroids act through multiple molecular pathways and mechanisms that make a consensus difficult. Research on the action of different steroids in the field of rhinology may lead to a systematic use focused on more specific pre-or postoperative indications.…”
Section: Discussionmentioning
confidence: 99%
“…При этом в большинстве случаев перфорация была выявлена у молодых женщин в течение первых 12 мес от начала терапии [8]. Авторы другого исследования [9] скептически относятся к возможности возникновения атрофии слизистой оболочки полости носа под влиянием ИКС. Отмечено, что из 34 соответствующих публикаций термин «атрофия» слизистой оболочки полости носа упоминался в 17 статьях.…”
unclassified
“…При этом определение термина приводилось только в 10 публикациях, а в остальных оно значительно варьировало, отсутствовали также четкие гистологические доказательства повреждающего влияния ИКС на слизистую оболочку полости носа. Авторы отмечают, что связь между использованием ИКС и возникновением атрофии слизистой оболочки полости носа является мифом независимо от показаний, типа препарата, его дозы и длительности применения [9]. Такие же данные были получены в двух других независимых исследованиях.…”
unclassified